Digitization of entrepreneurial structures as a basis for their competitiveness - V. M. Mineeva (Путеводитель предпринимателя)
Flywheel of development of economic evolution of society is steadily swinging. The next coil of such development was the digitalization of the economy, which determines the relevance of the chosen theme. According to the author, who has affected all market participants, including entrepreneurial structures, digitization significantly transforms them, increasing the competitiveness of the latter. In connection with this there is a need to clarify how digitization transforms the enterprise. The purpose of writing the article is to consider digitization of entrepreneurial structures as a basis for their competitiveness. The subject of the research is digitization. The methodology is based on the logical and systemic approaches, the methods of comparative and system analysis are used to solve individual problems. The research conducted by the author has shown that the strategies of digital transformation should be subject to constant reassessment, which evaluates both the initial assumptions and progress in transformation to date. However, it should be noted that existing scientific approaches consider certain aspects of the investigated issues, consideration of problems of the general influence of tendencies of the digital economy on practical activity of entrepreneurial structures in Have not received the proper theoretical justification and practical solution at present. This article will be interesting for researchers in the field of entrepreneurship, studying the development of entrepreneurship in the conditions of digitalization of the economy.